A study on the fabrication and microwave shielding properties of PANI/C60 heterostructures - Lin, Tengfei; Yu, Haojie; Wang, Li; Ma, Qinghua; Huang, Haiyu; Wang, Li; Uddin, Md Alim; Haq, Fazal; Lemenovskiy, Dmitry A. (Polymer composites, 2021)
The in‐situ chemical oxidative polymerization was introduced to prepare the composites of polyaniline/fullerene (PANI/C60) in this work. The effects of different reaction conditions such as the concentration of C60, the concentration of doping acids, the concentration of aniline (ANI), and the reaction temperature were investigated. The composites were characterized by FTIR, scanning electron microscopy, transmission electron microscope, X‐ray diffraction, TGA, X‐ray photoelectron spectroscopy, and vector network analyzer measurements. The electromagnetic interference (EMI) shielding properties were evaluated over the frequency range of 1.0–4.5 GHz, and it was found that the average total EMI SE was 23.01 dB with additional content of 50 wt% the optimized PANI/C60 composite powder, which contains ~97.26 wt% of PANI (mainly nanorods) and ~2.74 wt% of C60 in the paraffin wax matrix. The possible composites formation mechanism and EMI shielding mechanism for PANI/C60 composites were discussed. The relationship between the conductivities of the samples and the EM shielding performance was also investigated.